From gut to placenta: understanding how the maternal microbiome models life-long conditions - Ruiz-Triviño, Jonathan; Álvarez, Daniel; Cadavid J., Ángela P.; Alvarez, Angela M. (Frontiers in Endocrinology, 2023)
The microbiome -defined as the microbiota (bacteria, archaea, lower and higher eukaryotes), their genomes, and the surrounding environmental conditions-has a well-described range of physiological functions. Thus, an imbalance of the microbiota composition -dysbiosis-has been associated with pregnancy complications or adverse fetal outcomes. Although there is controversy about the existence or absence of a microbiome in the placenta and fetus during healthy pregnancy, it is known that gut microbiota can produce bioactive metabolites that can enter the maternal circulation and may be actively or passively transferred through the placenta. Furthermore, the evidence suggests that such metabolites have some effect on the fetus. Since the microbiome can influence the epigenome, and modifications of the epigenome could be responsible for fetal programming, it can be experimentally supported that the maternal microbiome and its metabolites could be involved in fetal programming. The developmental origin of health and disease (DOHaD) approach looks to understand how exposure to environmental factors during periods of high plasticity in the early stages of life (e.g., gestational period) influences the program for disease risk in the progeny. Therefore, according to the DOHaD approach, the influence of maternal microbiota in disease development must be explored. Here, we described some of the diseases of adulthood that could be related to alterations in the maternal microbiota. In summary, this review aims to highlight the influence of maternal microbiota on both fetal development and postnatal life, suggesting that dysbiosis on this microbiota could be related to adulthood morbidity.